Authentication without Identification. - Lysyanskaya, A.
Many authentication transactions performed today require us to disclose more information than is strictly needed, just for verification purposes. Fortunately, modern cryptography provides us with a way to solve the verification problem without leaking unnecessary personal information. These techniques are fast, secure, and preserve privacy.